2000
DOI: 10.1046/j.1525-139x.2000.00104.x
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Safety of Intravenous Iron Dextran, Iron Saccharate, and Sodium Ferric Gluconate

Abstract: Intravenous iron treatment is an important component of anemia therapy for patients on dialysis. Until recently iron dextran was the only parenteral form of iron available in the United States. This drug has been associated with occasional serious adverse reactions, including full-blown anaphylaxis. In 1999 the Food and Drug Administration approved a second form of iron for intravenous administration, sodium ferric gluconate in sucrose. It is expected that by the time of this publication, a third agent, iron s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
77
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 26 publications
(27 reference statements)
1
77
0
1
Order By: Relevance
“…[28] Given the rarity of true allergic events, the utility of a test dose especially for non-dextran molecules like the SFGC is debatable. [3,30] In the present study, a one-time test dose was given to patients receiving ID or SFGC as per the latest EBPG guidelines. [3] In the present study, a history of prior drug allergy, iron dextran use, and prior reaction to i.v.…”
Section: Discussionmentioning
confidence: 99%
“…[28] Given the rarity of true allergic events, the utility of a test dose especially for non-dextran molecules like the SFGC is debatable. [3,30] In the present study, a one-time test dose was given to patients receiving ID or SFGC as per the latest EBPG guidelines. [3] In the present study, a history of prior drug allergy, iron dextran use, and prior reaction to i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Iron is usually substituted by intravenous iron (iv.Fe), because oral supplementation is inefficient (3)(4)(5)(6). Despite the acknowledged safety of iv.Fe preparations such as ferric saccharate (7)(8)(9), the occurrence of non-transferrin-bound iron (NTBI) in the plasma of patients has been reported, either directly (10 -14) or indirectly, by detection of enhanced symptoms of oxidative stress (15)(16)(17)(18), of neutrophil damage (19), of support of bacterial growth (11), or increased incidence of infectious diseases (20,21).…”
mentioning
confidence: 99%
“…3 Other studies have reported similar high rates of allergic reactions for iron dextran. [4][5][6] As a result, several authors have advocated the use of iron gluconate over iron dextran, in order to avoid serious reactions. For example, The University of Iowa Health Care Center uses only iron gluconate despite the need for multiple dosing.…”
mentioning
confidence: 99%